Odpowiedź :
Szczegółowe wyjaśnienie:
Zad. 3
a) -(2x - 1) = 4
-2x + 1 = 4
-2x = 4 - 1
-2x = 3
x = - 1,5
b) 2(x + 1) = x
2x + 2 = x
2 = x - 2x
2 = - x
x = -2
c) 2t - (3t + 1) = 6
2t - 3t - 1 = 6
-t = 6 + 1
-t = 7
t = -7
d) -(4 - x) = 2(3 - x)
-4 + x = 6 - 2x
x + 2x = 6 + 4
3x = 10
x = 3/10
e) 3(y + 6) - y = 2(y + 9)
3y + 18 - y = 2y + 18
3y - y - 2y = 18 - 18
0 = 0
f) x + 7 - 2(3x + 5) = 3
x + 7 - 6x - 10 = 3
x - 6x = 3 - 7 + 10
-5x = 6
x = - 1,2
Zad. 4
a) x + 2x = x + 9
3x = x + 9
3x - x = 9
2x = 9
x = 4,5
b) y + 2y - 5 = 11 - y
y + 2y +y = 11 + 5
4y = 16
y = 3
c) 3a + 4 = a - 1 + a + 7
3a - a - a = -1 + 7 - 4
a = 2
d) 10 - 2b + 6 + b = 10 - b + 4 - b
-2b + b + b + b = 10 + 4 - 10 - 6
b = -2